Endocrine mucin-producing sweat gland carcinoma of eyelid as a presenting feature of breast carcinoma in a male patient - Tanisha Sehgal; Ritesh Verma; Aminder Singh; Yesha Gupta (Oman Journal of Ophthalmology, 2025)
Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a rare indolent tumor with predilection for periocular skin of elderly women. Although recurrences may occur, metastases are uncommon with EMPSGC. We present a case of EMPSGC of the eyelid as a presenting feature of invasive carcinoma of the breast in a male patient. A 71-year-old male presented with a right eyelid mass from the past 6 months. A wide excision biopsy with intraoperative frozen section margin control and reconstruction was done. Histopathology and immunohistochemistry (IHC) were suggestive of EMPSGC. On systemic examination, the patient had a breast mass 2 cm × 3 cm × 1 cm which he did not reveal at presentation. A Trucut biopsy was performed, and the histopathology was similar to the eyelid tumor. On positron emission tomography (PET) scan, there was uptake in the breast mass, axillary and mediastinal lymph nodes, and multiple nodular lesions in the lungs were noted. The patient underwent BRCA1/2 mutation test which revealed a variance of uncertain significance. In view of hormone receptor positivity, the patient was then started on hormonal therapy and the tumor showed significant regression on serial examination and successive PET scans. We discuss the management of the eyelid lesion and compare the histopathology and IHC of the primary and metastatic tumor.